Elucidating the role of androgen receptor in breast cancer. (October 2012) - Lim, Elgene; Ni, Min; Hazra, Aditi; Tamimi, Rulla; Brown, Myles
The androgen receptor (AR) is expressed in the majority of breast cancers and can be effectively targeted with both AR agonists and anti-androgen therapies. AR expression and its prognostic implications vary according to breast cancer subtype. We will review the prognostic effect of AR expression, and discuss recent preclinical studies that have shed light on AR signaling and its interactions with other signaling pathways according to breast cancer subtype. Finally, we will discuss AR inhibitors that have been evaluated in early-phase clinical trials and that are under development. We will also discuss novel mechanistic insights and combinatorial therapeutic strategies that have been developed in preclinical studies with the potential to translate into effective clinical strategies for AR + breast cancer.